2022
DOI: 10.1016/j.cub.2022.01.028
|View full text |Cite
|
Sign up to set email alerts
|

A bacterial endosymbiont of the fungus Rhizopus microsporus drives phagocyte evasion and opportunistic virulence

Abstract: A bacterial endosymbiont of the fungus Rhizopus microsporus drives phagocyte evasion and opportunistic virulence Highlights d Bacterial endosymbionts protect fungal spores from phagocytes d A secreted factor blocks growth and killing by environmental amoebas d Endosymbionts improve fungal stress resistance d Endosymbiosis also allows the evasion of vertebrate immune cells and virulence in vivo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 129 publications
(232 reference statements)
1
39
0
Order By: Relevance
“…S1A in the supplemental material), which are significantly larger than dormant spores (5.2 μm ± 0.5 μm, unpaired t test: t = 5.93, df = 3.2, P = 0.0081; see Table S1A ). A reduced uptake of swollen R. microsporus spores was previously also reported for macrophages ( 35 ). Although the increase in spore size makes it difficult for P. aurantium (mean diameter of approximately 13.2 μm ± 2.2 μm) to ingest swollen spores, in some rare cases we observed phagocytosis of swollen spores and R. microsporus germlings (see Fig.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…S1A in the supplemental material), which are significantly larger than dormant spores (5.2 μm ± 0.5 μm, unpaired t test: t = 5.93, df = 3.2, P = 0.0081; see Table S1A ). A reduced uptake of swollen R. microsporus spores was previously also reported for macrophages ( 35 ). Although the increase in spore size makes it difficult for P. aurantium (mean diameter of approximately 13.2 μm ± 2.2 μm) to ingest swollen spores, in some rare cases we observed phagocytosis of swollen spores and R. microsporus germlings (see Fig.…”
Section: Resultssupporting
confidence: 80%
“…However, ingestion of spores has lethal consequences for the amoeba when R. microsporus spores contain the toxin-producing endosymbiont ( 5 ). Although it was previously suggested that Ralstonia pickettii , an endosymbiont of R. microsporus , secretes growth suppressing factors against the soil-dwelling amoeba Dictyostelium discoideum ( 35 ), we present the first report of rhizoxin-mediated killing of a fungivorous amoeba. These results highlight that endosymbionts protect their fungal host from being attacked by mycophagous amoeba.…”
Section: Discussionmentioning
confidence: 84%
“…To evade predation, R. microsporus relies on molecules secreted by its endosymbiont bacterium Ralstonia pickettii , which interfere with phagocytosis by D. discoidenum (Itabangi et al . 2022 ). Interestingly, this anti-phagocyte activity also protects R. microsporus from clearance by human macrophages during opportunistic infections, and R. microscopus virulence is greatly reduced in absence of the endosymbiont (Itabangi et al .…”
Section: Fungal Effector-mediated Manipulation Of Plant Host Microbiotamentioning
confidence: 99%
“…Interestingly, this anti-phagocyte activity also protects R. microsporus from clearance by human macrophages during opportunistic infections, and R. microscopus virulence is greatly reduced in absence of the endosymbiont (Itabangi et al . 2022 ). Hence, the recruitment of microbial symbionts can extend the virulence potential of fungal pathogens and, possibly, effector proteins could play a role in such a recruitment.…”
Section: Fungal Effector-mediated Manipulation Of Plant Host Microbiotamentioning
confidence: 99%
“…Endosymbiotic bacteria are related to plant infection through the production of rhizoxin, a toxin that blocks plant cell mitosis and necrotizes plant tissue, favoring the development of R. microsporus [ 100 ]. Regarding mucormycosis, these symbiotic bacteria drive phagocyte evasion and opportunistic virulence [ 102 ].…”
Section: Genetic Manipulation In Mucorales and New...mentioning
confidence: 99%